An analysis of the possible protective effect of antipsychotics for SARS-CoV-2 in patients under treatment for severe mental illnesses - Prokopez, Cintia R. (2021)
Since the Severe Acute Respiratory Syndrome coronavirus type 2 (SARS-CoV-2) pandemic has sparked, it was supposed that inpatients with severe mental illnesses (SMI) could be at higher risk of developing the infection, as a consequence of their long stay in closed institutions, adding to the difficulty that SMI entails for compliance with prevention measures, like social distancing or mask wearing. Moreover, people with SMI usually tend to have unhealthy habits, including the use of high amounts of tobacco, a sedentary lifestyle, and an inappropriate diet. These factors, added to the metabolic adverse effects associated with the use of atypical antipsychotics, predispose to respiratory, cardiovascular, and metabolic diseases (Rossler, Salize et al. 2005). It is well known that all these conditions are associated with a severe course of SARS-CoV-2 disease (Chen, Wu et al. 2020, Grasselli, Greco et al. 2020, Zheng, Peng et al. 2020). Since the pandemic started in Argentina, we expected a growing number of infected inpatients among mental health hospitals. To prevent the SARS-CoV-2 spread among patients in closed institutions, a SARS-CoV-2 unit was created to receive all inpatients with a positive test and the absence of symptoms, or the presence of mild symptoms. To our surprise, these units received few patients, and even fewer patients required to be transferred to more complex general hospitals because of the disease severity. These events led us to ask if antipsychotics could have a protective effect on the disease.